600 new students join UMP - Siti Nur Azwin, Zulkapri (UMPSA, 2023)
PAYA BESAR, 22 July 2023 - Joy was in the air when parents and families attended the recent registration session of diploma and Science and Technology Foundation students for the 2023/2024 academic session at Universiti Malaysia Pahang (UMP).